(untitled) (Global Journal of Management and Business Research, 2020)
The main aim of the study was to assess moderating role of organizational citizenship behaviour on relationship between employee political skill and employee performance in Kenyan universities. The study was grounded by social exchange theory. The study used positivism paradigm, explanatory research design, simple and combination of random and stratified sampling on a target population of 6147 employees in selected universities in Kenya. A sample size of 567 academic and non-academic staff selected based on Yamane’s formula to determine selection of respondents to be served with structured questionnaires. The reliability of the data collection instrument was presented using Cronbach Alpha while factor analysis was used to validate the instrument. Data was analysed quantitatively with the aid of the Statistical Package for Social Science (SPSS 24.0).